Integrating Digital Governance for Disaster Resilience: A TOGAF 10-Based Enterprise Architecture for Coastal Villages in Eretan Wetan, Indonesia - Hasanah, Sofiyatun; Fajrillah, Asti Amalia Nur; Mukti, ⁠Iqbal Yulizar (Jurnal Teknik Informatika (Jutif), 2026)
Indonesia's coastal regions face significant challenges due to climate change and natural disasters such as coastal abrasion, tidal flooding, and high waves, which impact the social and economic sustainability of rural communities. One of the vulnerable areas is Eretan Wetan Village, Kandanghaur Subdistrict, Indramayu Regency, which has a low score of 5.88 for SDGs Goal 13 (Climate Action Village). This studyse aims to design an Enterprise Architecture to support the implementation of a more effective, structured, and sustainable Coastal Disaster-Resilient Village (Destana). The design adopts the TOGAF 10 framework, covering the phases of Preliminary, Architecture Vision, Business Architecture, Data Architecture, Technology Architecture, Opportunities and Solutions, and Migration Planning. The outcome of this study includes an architectural blueprint and IT roadmap, which are expected to serve as a strategic guide for the village government in developing an integrated and adaptive disaster management system. Through this approach, Eretan Wetan Village is expected to enhance disaster preparedness, strengthen stakeholder coordination, and contribute to the achievement of sustainable development goals. This study shows how important it is in the field of information systems to solve real-world problems in rural regions through digital system integration.